Sensitive Periods for Developing a Robust Trait of Appetitive Aggression - Köbach, Anke; Elbert, Thomas (Frontiers in Psychiatry, 2015)
Violent behaviour can be intrinsically rewarding; especially combatants fighting in current civil wars present with elevated traits of appetitive aggression. The majority of these fighters were recruited as children or adolescents. In the present study we test whether there is a developmental period where combatants are sensitive for developing a robust trait of appetitive aggression. We investigated 95 combatants in their demobilization process that were recruited at different ages in the Kivu regions of the eastern Democratic Republic of Congo. Using random forest with conditional inference trees, we identified recruitment at the ages from 16 and 17 years as being predictive of the level of appetitive aggression; the number of lifetime, perpetrated acts was the most important predictor. We conclude that high levels of appetitive aggression develop in ex-combatants, especially in those recruited during their middle to late teenage, which is a developmental period marked by a natural inclination to exercise physical force. Consequently, ex-combatants may remain vulnerable for aggressive behaviour patterns and re-recruitment unless they are provided alternative strategies for dealing with their aggression.